Job Satisfaction: Impact On Employee Discipline Of Pt. Sago Nauli Sinunukan - Tira Anisa; Suhartini Suhartini (CV. Syntax Corporation Indonesia, 2023)
This study focuses on the problem of job dissatisfaction which has an impact on the level of discipline of employees in the office division of PT Sago Nauli. The research object was chosen because of the frequent disciplinary problems that arise such as absenteeism, tardiness, and other violations due to job dissatisfaction. The research sample includes all office division employees, totaling 16 people. The research uses quantitative methods and data collection techniques through observation, questionnaires and is supported by secondary data. Data analysis used descriptive statistical analysis and simple linear regression analysis with the help of the SPSS 20 for windows program. The results showed that the level of job satisfaction of office division employees was still low. Partially, the variable job satisfaction (X) has a positive and significant effect on work discipline (Y) for office division employees at PT Sago Nauli.